135 A Comparison of Outcomes Between Deep Brain Stimulation Under General Anesthesia Versus Conscious Sedation With Awake Evaluation. (1st August 2016) - Alesch, François; Jain, Roshini; Chen, Lilly; Brucke, Thomas; Seijo, Fernando; San Martin, Esther Suarez; Haegelen, Claire; Verin, Marc; Maarouf, Mohammed; Barbe, Michael T.; Gill, Steven; Whone, Alan; et al.
Abstract: INTRODUCTION: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) for the management of motor symptoms of Parkinson disease (PD) is typically performed under conscious sedation with awake evaluation during intraoperative physiologic testing. However, developments in surgical techniques now allow for subjects to be asleep during the procedure using general anesthesia. Previously reported long-term outcomes of subjects who underwent STN-DBS under general anesthesia demonstrated postoperative safety and efficacy out to 1 year. In this study, we examine outcomes between subjects undergoing the STN-DBS procedure who used general anesthesia vs those using conscious sedation with awake evaluation as part of the ongoing VANTAGE clinical trial. METHODS: VANTAGE is a prospective, multicenter, nonrandomized, open-label interventional trial, sponsored by Boston Scientific Corporation. The trial assesses motor improvement in subjects with moderate-to-severe PD following bilateral STN-DBS. Assessments include motor scores such as Unified Parkinson's Disease Rating Scale (UPDRS) and quality-of-life measurements such as PDQ-39. Forty subjects were implanted bilaterally with the Vercise DBS System (Boston Scientific Corporation) at 6 European centers. Of these, 19 (47%) underwent the DBS procedure under general anesthesia. RESULTS: Analysis of both study groups did not indicate a statistically significant difference in motor function outcomes. However, subjects utilizing general anesthesia were found not to display motor function outcomes that were necessarily clinically inferior to those consciously sedated with awake evaluation. Sample size and variation in baseline differences in selected subjects may have contributed to these final results, because a tendency for subjects undergoing general anesthesia to report an improvement in motor function similar to or better than those consciously sedated (vs baseline) was observed. CONCLUSION: No inferiority in clinical outcomes was observed in subjects that underwent general anesthesia vs those that were consciously sedated with awake evaluation.